2018
DOI: 10.1080/14712598.2018.1454427
|View full text |Cite
|
Sign up to set email alerts
|

Ecto-F0/F1 ATPase as a novel candidate of prothymosin α receptor

Abstract: The present study suggests that ProTα may activate ecto-F/F ATPase and produced ATP. This study leads to next subjects whether produced ATP and its metabolites, ADP or adenosine may activate corresponding G-coupled receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…In PIT ischemia model, P6Q treatment with tPA upto 6 h also inhibited brain damage without hemorrhage and motor dysfunction evaluated by Rotarod test. The next important goal will be to clarify the molecular-and cellular-based mechanisms underlying ProTa-or P6Qinduced beneficial effects against the cellular damage using a combination of ischemia/reperfusion and tPA using CLARITY system in the brain and vascular cell culture system, as we recently reported two candidate receptors for ProTa, which are TLR4 and plasma F0/F1 ATPase in the plasma membrane (Halder et al 2015;Ueda et al 2018). As the beneficial effects of ProTa/P6Q are apparent despite the small sample size, future experiments will be performed using additional number of animals and a more detailed histological analysis to permit a more thorough analysis of different parameters, including dose optimization and therapeutic window.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PIT ischemia model, P6Q treatment with tPA upto 6 h also inhibited brain damage without hemorrhage and motor dysfunction evaluated by Rotarod test. The next important goal will be to clarify the molecular-and cellular-based mechanisms underlying ProTa-or P6Qinduced beneficial effects against the cellular damage using a combination of ischemia/reperfusion and tPA using CLARITY system in the brain and vascular cell culture system, as we recently reported two candidate receptors for ProTa, which are TLR4 and plasma F0/F1 ATPase in the plasma membrane (Halder et al 2015;Ueda et al 2018). As the beneficial effects of ProTa/P6Q are apparent despite the small sample size, future experiments will be performed using additional number of animals and a more detailed histological analysis to permit a more thorough analysis of different parameters, including dose optimization and therapeutic window.…”
Section: Discussionmentioning
confidence: 99%
“…ProTa activates toll-like receptor 4 (TLR4) and its downstream TIR-domain-containing adapter-inducing interferon-b (TRIF) signaling to prevent the ischemic retina (Halder et al 2015). Recently, we reported that ProTa activates G i -coupled receptor ecto-F 0 /F 1 ATPase and produces ATP in HUVECs culture (Ueda et al 2018). We previously showed the protective effects of ProTa-derived 30-amino acid (a.a. 49-78) or 9-amino acid (a.a. 52-60) peptide in retinal and cerebral ischemia or serum-starvation stress (Halder et al 2013a;Halder et al 2013b).…”
mentioning
confidence: 99%